Evaluation of suspected cases of SARS-CoV-2 infection in children and adolescents in a hospital in Brazil (Research, Society and Development, 2021)
A COVID-19 is a disease caused by infection with the SARS-CoV-2 virus. The pediatric population corresponds to 1 to 5% of confirmed cases of the disease, varying according to the country under study. This work aims to analyze suspected and confirmed cases of children and adolescents of COVID-19 in a hospital in Sergipe. This is a cross-sectional observational study involving 1,388 patients, under 20 years of age, during March 2020 and September 2021. Among patients, 54.8% were male, 10.4% had some comorbidities. It was observed that dyspnea was related to age, being frequent in children. In addition, some clinical manifestations were associated with SARS-CoV-2 infection, such as headache (p=0.021), diarrhea (p=0.002), respiratory distress (p